The HIF transcription network exerts innate antiviral activity in neurons and limits brain inflammation - Farahani, Ensieh; Reinert, Line S.; Narita, Ryo; Serrero, Manutea C.; Skouboe, Morten Kelder; van der Horst, Demi; Assil, Sonia; Zhang, Baocun; Iversen, Marie B.; Gutierrez, Eugenio; Hazrati, Hossein; Johannsen, Mogens; et al. (Cell reports, 2024)
Pattern recognition receptors (PRRs) induce host defense but can also induce exacerbated inflammatory responses. This raises the question of whether other mechanisms are also involved in early host defense. Using transcriptome analysis of disrupted transcripts in herpes simplex virus (HSV)-infected cells, we find that HSV infection disrupts the hypoxia-inducible factor (HIF) transcription network in neurons and epithelial cells. Importantly, HIF activation leads to control of HSV replication. Mechanistically, HIF activation induces autophagy, which is essential for antiviral activity. HSV-2 infection in vivo leads to hypoxia in CNS neurons, and mice with neuron-specific HIF1/2α deficiency exhibit elevated viral load and augmented PRR signaling and inflammatory gene expression in the CNS after HSV-2 infection. Data from human stem cell-derived neuron and microglia cultures show that HIF also exerts antiviral and inflammation-restricting activity in human CNS cells. Collectively, the HIF transcription factor system senses virus-induced hypoxic stress to induce cell-intrinsic antiviral responses and limit inflammation.
Online verfügbar: 15. Februar 2024
Gesehen am 29.07.2024